Nuclear translocation of MRTFA in MCF7 breast cancer cells shifts ERα nuclear/genomic to extra-nuclear/non genomic actions. (15th June 2021) - Jehanno, Charly; Percevault, Frédéric; Boujrad, Noureddine; Le Goff, Pascale; Fontaine, Coralie; Arnal, Jean-François; Primig, Michael; Pakdel, Farzad; Michel, Denis; Métivier, Raphaël; Flouriot, Gilles
Abstract: The Myocardin-related transcription factor A [MRTFA, also known as Megakaryoblastic Leukemia 1 (MKL1))] is a major actor in the epithelial to mesenchymal transition (EMT). We have previously shown that activation and nuclear accumulation of MRTFA mediate endocrine resistance of estrogen receptor alpha (ERα) positive breast cancers by initiating a partial transition from luminal to basal-like phenotype and impairing ERα cistrome and transcriptome. In the present study, we deepen our understanding of the mechanism by monitoring functional changes in the receptor's activity. We demonstrate that MRTFA nuclear accumulation down-regulates the expression of the unliganded (Apo-)ERα and causes a redistribution of the protein localization from its normal nuclear place to the entire cell volume. This phenomenon is accompanied by a shift in Apo-ERα monomer/dimer ratio towards the monomeric state, leading to significant functional consequences on ERα activities. In particular, the association of Apo-ERα with chromatin is drastically decreased, and the remaining ERα binding sites are substantially less enriched in ERE motifs than in control conditions. Monitored by proximity Ligation Assay, ERα interactions with P160 family coactivators are partly impacted when MRTFA accumulates in the nucleus, and those with SMRT and NCOR1 corepressors are abolished. Finally, ERα interactions with kinases such as c-src and PI3K are increased, thereby enhancing MAP Kinase and AKT activities. In conclusion, the activation and nuclear accumulation of MRTFA in ERα positive breast cancer cells remodels both ERα location and functions by shifting its activity from nuclear genome regulation to extra-nuclear non-genomic signaling. Highlights: MRTFA is a master regulator of actin dynamic and cellular motile functions. Nuclear translocation of MRTFA is associated with endocrine resistance. Nuclear translocation of MRTFA down-regulates ERα and relocates it to the whole cell. Nuclear translocation of MRTFA induces a shift in Apo-ERα monomer/dimer ratio towards the monomeric state. Nuclear translocation of MRTFA abolishes ERα interactions with corepressors and promotes ER interactions with kinases.